PELAKSANAAN PERKAWINAN PARU DHEKO DALAM HUKUM ADAT SUKU ENDE DI DESA RAPORENDU KECAMATAN NANGAPANDA KABUPATEN ENDE - Marvianti Pua. A; Yuliatin; Edy Kurniawansyah; Rispawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the process of implementing paru dheko marriage (elopement) in the customary law of the Ende Tribe, as well as the factors that cause paru dheko marriage in Raporendu Village, Nangapanda District, Ende Regency. This research uses a qualitative approach with ethnographic research type. Based on the results of the study, the implementation of paru dheko (elopement) marriage in the customary law of the Ende Tribe is divided into three stages, namely the initial stage of five customary processions, the core stage of seven customary processions, and the closing stage of two customary processions. A paru dheko marriage is considered to violate the provisions of traditional marriage as it should be, so the consequence is that there is no provision of belis for women and the entire burden of marriage is borne by the male party. In a customary perspective, paru dheko marriages are still regulated in the Ende tribe's customary legal system to prevent conflict and maintain family honor. The factors that cause the occurrence of paru dheko are divided into two, namely internal factors such as the couple's personal desire and pregnancy outside marriage, and external factors such as the high cost of belis, family disapproval, differences in social status, and social environmental pressure.